Contribution of FACTS Devices to the Transient Stability Improvement of a Power System Integrated with a PMSG-based Wind Turbine - Akpeke, N. E.; Muriithi, C. M.; Mwaniki, C. (Engineering, Technology & Applied Science Research, 2019)
The increasing penetration of wind energy to the conventional power system due to the rapid growth of energy demand has led to the consideration of different wind turbine generator technologies. In fault conditions, the frequency of the power system decreases and eventually leads to speed differences between the grid and the interconnected wind generator. This can result to power system problems such as transient instability (TS). This paper focuses on enhancing the TS of a permanent magnet synchronous generator (PMSG)-based power system during 3ph fault conditions using FACTS devices. The power system considered is connected to a large wind farm which is based on PMSG. Critical clearing time (CCT) is used as an index to evaluate the transient state of the system. Under the study of an IEEE-14 bus system using PSAT as a simulation tool, the integrated CCT with PMSG-based wind turbine is improved with three independent FACTS devices. One of the synchronous generators in the test system has been replaced at random with the PMSG-based wind turbine which is meant to generate an equivalent power. Time domain simulations (TDSs) were carried out considering four study cases. Simulation results show that the (CCT) of the system with the FACTS devices is longer than the CCT without them, which is an indication of TS improvement.